﻿Spontaneous vascular flora of the historical monumental cemetery of Modena (N-Italy) - Fabrizio Buldrini; Ilaria Gianaroli; Giovanna Bosi; Alessandro Alessandrini; Claudio Santini (Italian Botanist, 2023)
The first floristic study of the historical monumental cemetery of San Cataldo in Modena (N-Italy) is presented. The research was performed in the period 2019–2022, considering only spontaneous individuals growing within the historical area (4.8 ha). A total of 266 taxa (species and subspecies) was found, of which 1 new for the flora of Italy (Malus × robusta ‘John Downie’), 2 new for the administrative region of Emilia-Romagna (Calocedrus decurrens and Salvia haematodes) and 1 new for the province of Modena (Epilobium ciliatum). Therophytes prevail (37.6%), followed by hemicryptophytes (31.6%), phanerophytes (16.2%) and geophytes (11.7%). The chorological spectrum is dominated by Eurasian species (32.0%), followed by Mediterranean (26.3%), Cosmopolitan (24.8%), Boreal (6%) and N-American (4.5%) ones. Allochthonous species are 16.5% of the list, with neophytes always prevailing over archaeophytes (28 vs. 9 species). Invasive species are 67.8% of the neophytes; on a regional scale they are 1.5% of the list. Protected species are 2.6% of the total; 3 of them are internationally protected and 2 are included in the red list of Italian flora. This study confirms the great biological richness of urban environments and the potential of historical cemeteries as a refugium for the conservation of species that have become rare, endangered or infrequent at a regional or national level, because of the heavy human impact on the territory.